Innovation, Employment and Growth Policy Issues in the EU and the US - Welfens, Paul J.J.; Addison, John T. (Springer Berlin Heidelberg, 2009)
The EU and the U.S. confront distinct factor market dynamics and common policy challenges. Labor market developments and long-term changes in capital markets and capital flows represent key problems in aging societies. The analyses presented here compare the European and U.S. patterns in this regard. Moreover, Schumpeterian innovation dynamics as well as energy policy issues receive attention. Considerable differences in innovation dynamics are reported across countries. The book charts the role of different innovation systems and knowledge societies and highlights different policy approaches. Another focus is upon structural changes and innovation in open economies. Finally, medium and long-term options for transatlantic cooperation are evaluated against the backdrop of the Lisbon agenda.